Manejo de efluentes líquidos mediante gestión ambiental en el camal del distrito el porvenir. - Angulo Zavaleta, Karin Jannet (2011)
The most important sectors in the Province of Trujillo, are: "Trade Wholesale and Retail" (49%) and "Industry" (13%). Both account for 62% of all local operators. As the industry one of the most decentralized activities, industry 48% is done outside the Trujillo district. The district of El Porvenir, is one of the locations that concentrates the development of activities in industry and manufacturing industry (presence of tanneries, slaughterhouses, etc.), and the largest contributor to the department. Its natural, human and capital resources place it among the most important in the province of Trujillo, it reflects an "emerging industrial" activity, developed mainly in the central district and surrounding avenues; the same that impact the environment polluting the air, soil and subsoil, and causing deterioration of facilities and the sewage system (mainly by the presence of organic residues) not only the town but also the infrastructure of water treatment residual of the metropolis, which is not prepared to treat this waste. This paper aims to develop an environmental management system for wastewater in the slaughterhouse district El Porvenir, based on the ISO 14001 standards and the fundamental principles of environmental management system: implementation of clean technology and preventive actions before corrective. The initial evaluation was conducted between March and November 2010 which concludes that the slaughterhouse wastewater exceeds the limits set by current regulations: suspended solids BOD5 8.5 ml / L / h, oils and fats 100 mg / L; so that proper management of wastewater is necessary. To this end, the environmental impacts in municipal slaughterhouses are determined, the preventive measures of potential impact caused by waste impacts and methods of pollution control are given is identified.